Feasibility and effectiveness of a group therapy combining physical activity, surf therapy and cognitive behavioral therapy to treat adolescents with depressive disorders: a pilot study - Bettina Hearn; Monica Biscaldi; Reinhold Rauh; Christian Fleischhaker (Frontiers in Psychology)
IntroductionThe high prevalence of depression among adolescents underlines the need for further research into effective treatment options. Previous research has demonstrated the effectiveness of physical activity in reducing depressive symptoms. Recently, studies on surf therapy, as an innovative approach of physical activity, have shown promising results regarding the reduction of depressive symptoms in adults and the improvement of general mental health problems in adolescents. However, research in this area is still limited. The aim of the current study was to investigate the feasibility and effectiveness of a group therapy program that combines physical activity, including surf therapy, with cognitive behavioral therapy for treating depression among adolescents.MethodsThirty-two outpatients (28 female, four male) aged 13–18 years with a mean age of 15.58 years (SD = 1.52) and a primary diagnosis of depression were included. They participated in a 3-month group therapy program in groups of eight adolescents. The dropout rate was calculated as an aspect of feasibility. To evaluate effectiveness, depressive symptoms were assessed using the “Children's Depression Rating Scale–Revised” (CDRS-R) as the primary outcome measure at pre-program, post-program, and at 3-month follow-up. In addition, questionnaires assessing depressive symptoms [“Beck Depression Inventory II” (BDI-II)], emotion regulation strategies [“Fragebogen zur Erhebung der Emotionsregulation bei Kindern und Jugendlichen” (FEEL-KJ)] and self-esteem [“Selbstwertinventar für Kinder und Jugendliche” [SEKJ)] were administered as secondary outcome measures.ResultsResults showed a low dropout rate of 9.38% (n = 3). Depressive symptoms, assessed by the CDRS-R, were significantly reduced over time, with a large effect size. Symptom reductions were maintained at the 3-month follow-up.DiscussionStudy results suggest that the group therapy program is feasible and can reduce depressive symptoms. Further research that includes control groups is needed. As a clinical implication, novel treatment forms which integrate elements of physical activity, should be considered as a treatment option for depressed adolescents